2011
DOI: 10.1007/s10067-011-1758-6
|View full text |Cite
|
Sign up to set email alerts
|

How common is methotrexate pneumonitis? A large prospective study investigates

Abstract: The current literature states the prevalence of methotrexate pneumonitis (MTX-P) to be 3.5-7.6%. This is based on retrospective data. Consequently, clinicians remain cautious in using methotrexate especially in patients with pre-existing lung disease. To get a true idea of the incidence of MTX-P we designed an ongoing prospective study, which is the largest to date. We recruited all patients starting low-dose methotrexate in our department, and followed them up for 2 years or until development of MTX-P. All pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 11 publications
0
41
0
2
Order By: Relevance
“…Interestingly, in patients with pulmonary fibrosis, MTX did not cause any deterioration in pulmonary function over a 2-yr period. In another study of Sathi et al [30], MTX has not been shown to accelerate the progression of underlying ILD in RA [15].…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, in patients with pulmonary fibrosis, MTX did not cause any deterioration in pulmonary function over a 2-yr period. In another study of Sathi et al [30], MTX has not been shown to accelerate the progression of underlying ILD in RA [15].…”
Section: Discussionmentioning
confidence: 97%
“…16 In a recent study (2012) Sathi et al reported an incidence of one case every 192 patient years. 17 The same group in 2008 had reported a prevalence of 1%(2/211). According to them MTX-P is rare.…”
Section: Acute Interstitial Pneumonitismentioning
confidence: 93%
“…25 Sathi et al (2012) suggest that baseline spirometry rather than full pulmonary function tests can be used routinely, prior to starting MTX. However in their study they did not find any specific base-line abnormalities in patients who developed MTX-P. 17 The role of preexisting lung disease on the development of MTX-pulmonary toxicity has been debated. Golden et al (1995) studied 93 women and 32 men with RA treated with MTX.…”
Section: Risk Factorsmentioning
confidence: 97%
See 2 more Smart Citations